Evaluating the impact of varying protein source and ammonium chloride inclusion on feedlot goat growth and carcass traits - Ewing, Erika A.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The purpose of this study was to determine the different protein sources and ammonium chloride inclusion and its effects on growth and carcass traits in Boer goats. Our hypothesis was the replacement of DDGS with Soyplus and the replacement of ammonium chloride with Soychlor would have an impact on the weight gained, carcass quality, and the pH of goat urine as well as results in a reduced feed cost. Seventy-five meat goat kids (approximately 70 d of age) were used in a completely randomized design. Animals were housed at the KSU Sheep and Meat Goat Center with 3 kids per pen (5 pens per treatment for 42 days). Kids were allotted into one of 5 experimental diets: 1) Soybean meal (SBM); 2) Dried distillers' grain saluables (DDGS); 3) Soyplus; 4) SBM plus SoyChlor; and 5) Soyplus plus SoyChlor. Diet costs include Treatment 1) $150.67/ton; Treatment 2) $125.04/ton; Treatment 3) 162.76/ton; Treatment 4) $172.76/ton; and Treatment 5) $178.25/ton. Goats had ad libitium access to feed and water. Weights were recorded weekly of goats and feeders to determine; average daily feed intake (ADFI), average daily gain (ADG) and feed efficiency (G:F). The heaviest and lightest goats per pen were slaughtered and including hot carcass weight, yield, loin eye area, loin eye depth, fat depth at the 13th rib, and body wall thickness data was collected. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pen serving as the experimental unit. The results confirm that there was no significant difference in that SoyPlus(P>0.03) and SoyChlor(P>0.05) products did not have a noticeable effect on goats when compared to other feeds that were tested.
Keywords: Fall 2018